2020
DOI: 10.1016/j.devcel.2020.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating NAD+ Metabolism in Live Cells and In Vivo Using a Genetically Encoded Fluorescent Sensor

Abstract: Highlights d FiNad responds to subtle changes of NAD + metabolism in live cells and animals d The role of NAD + precursors in boosting NAD + levels is mapped in various organisms d Increased NAD + synthesis controls morphofunctional changes of activated macrophages d FiNad enables live-cell and in vivo imaging of NAD + decline during aging

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 54 publications
4
80
0
Order By: Relevance
“…In this work, we uncover how inter-cellular heterogeneity in metabolic state in breast cancer results from the combined variation in PI3K signaling, chromatin state, and actin dynamics ( Figures S7 H and S7I). Fluorescent biosensors have previously been used to perform high-content screens for metabolic perturbations, as well as interrogate metabolic features in vivo ; however, one under-explored feature that these tools provide is the ability to perform longitudinal single-cell analysis ( Takanaga et al., 2008 ; Zhao et al., 2015 ; Zou et al., 2020 ). Previous work using multiplex imaging of an AKT biosensor and AMPK FRET biosensor has shown that the cellular energetic state is synchronized with AKT activity ( Hung et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we uncover how inter-cellular heterogeneity in metabolic state in breast cancer results from the combined variation in PI3K signaling, chromatin state, and actin dynamics ( Figures S7 H and S7I). Fluorescent biosensors have previously been used to perform high-content screens for metabolic perturbations, as well as interrogate metabolic features in vivo ; however, one under-explored feature that these tools provide is the ability to perform longitudinal single-cell analysis ( Takanaga et al., 2008 ; Zhao et al., 2015 ; Zou et al., 2020 ). Previous work using multiplex imaging of an AKT biosensor and AMPK FRET biosensor has shown that the cellular energetic state is synchronized with AKT activity ( Hung et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Ca 2+ sensors, cpFP-based sensors to detect cofactors [ 94 ], cAMP [ 95 ], ATP [ 96 , 97 ], or neurotransmitters such as glutamate and GABA [ 98 , 99 ] were developed by inserting specific sensing domains to cp-FP. Different from these cytosolic cpFP-based sensors detecting diffusible signaling molecules, the cpFP-based voltage sensor, named ASAP, was designed by fusion of cpFP module to voltage-sensing domains tethered at plasma-membrane [ 100 , 101 ].…”
Section: Sensing Strategies Of Fp-based Biosensorsmentioning
confidence: 99%
“…Several genetically encoded sensors able to detect the NADH/NAD + ratio in living cells have been reported [ 204 , 205 ], but the absolute quantification of NAD + has only recently been obtained by Cambronne et al [ 206 ] who reported a radiometric sensor based on bacterial DNA-ligase and cpVenusFP (LigA-cpVenus), showing fluorescence reduction upon NAD + binding. Very recently, Zou et al [ 207 ] managed to obtain a sensor lighting in response to NAD + (FiNAD). “FiNad” is based on the insertion of cpYFP into the NAD + /NADH binding domain of the bacterial transcription repressor protein (T-Rex), optimized in order to recognize specifically NAD + .…”
Section: Fluorescence-based Biosensorsmentioning
confidence: 99%